Comparative Study of Punica granatum Gel and Triadent Oral Paste Effect on Recurrent Aphthous Stomatitis, a Double Blind Clinical Trial - Atefeh Tavangar; Abolfazl Aslani; Niloofar Nikbakht (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Recurrent aphthous stomatitis is a common oral lesion, and the use of herbal remedies containing tannin and flavonoid has been reported to be effective in treating aphthous stomatitis. Purpose: This study was aimed to evaluate the effect of Punica granatum muco-adhesive gel on controlling the oral recurrent aphthous stomatitis and its comparison with Triadent oral paste. Materials and Method: In this double-blind clinical trial, 60 patients with minor aphthous stomatitis were enrolled. These patients had no systemic diseases and were not on any medications. The patients were randomly treated with Punica granatum formulated gel, Triadent oral paste and placebo. The time of pain elimination and the time of complete healing were recorded and the pain degree was assessed and recorded by each patient. The data were analyzed using survival analysis and ANOVA test. Results: The Kaplan-Meier survival analysis demonstrated that pain relief time in Punica granatum group was lower than placebo group (p= 0.002), even so, it caused no significant difference with the Triadent group in comparison with the placebo group (p= 0.08). The survival analysis also indicated that the wound healing time in Punica granatum group was significantly lower than the other two groups (p< 0.05). Conclusion: Punica granatum gel has a successful effect in controlling and treating recurrent aphthous stomatitis. It can be considered as an affordable and inexpensive treatment.